Service Quality, Satisfaction and Patient Loyalty in Public Health Center of Bengkulu - Febriawati, Henni; Yandrizal, Yandrizal; Angraini, Wulan (Universitas Aisyah Pringsewu, 2022)
Loyalty services by patients depend on the quality of service received. Therefore, quality is the main competitive advantage and is an important aspect of a health service. In Bengkulu City, there were 156,854 people with a total contact rate of 15,726 (10.06%) with sick visits of 13,068 (8.33%) and healthy visits of 2,658 (1.69%). The high number of sick visits requires quality individual health services. The research design used was exploratory with a cross-sectional observational approach with hypothesis testing. And then to determine the relationship between the quality of curative services, quantitative methods, and qualitative methods, to determine the role of management in improving the quality of health services on patient satisfaction and customer loyalty in community health centre services. The results showed a significant relationship between the quality of health services and patient satisfaction and patient satisfaction with the customer loyalty to the community health centre in Bengkulu City (p = 0.001). Analysis of management improvements to improve the quality of achieving the health centre's indicator targets includes planning. So every three months, to discuss any problems in the implementation of each program, monitoring the assessment and evaluation of the implementation of activities at the community health centre carried out internally and externally. The services provided are good because the community health centre officers carry out efforts in service quality, especially in terms of the dimensions of empathy and physical evidence. Nevertheless, the community health centre should continue to improve service performance to meet the wishes and needs of patients with continuous and programmed efforts.Abstrak: ualitas pelayanan merupakan keunggulan bersaing yang utama dan perlu disadari bahwa kepuasan pasien merupakan aspek penting dalam suatu pelayanan kesehatan. Jika pelayanan yang diperolah memenuhi harapan pasien maka akan memunculkan minat memanfaatkan kembali penyedia pelayanan kesehatan tersebut. Di Kota Bengkulu terdapat sebanyak 156.854 jiwa dengan jumlah kontak rate 15.726 (10,06%) dengan kunjungan sakit sebanyak 13.068 (8,33%) dan kunjungan sehat 2.658 (1,69%). Masih tinggi angka kunjungan sakit menuntut pelayanan kesehatan perseorangan yang bermutu. Desain penelitian yang digunakan adalah eksploratori dengan pendekatan observasional Cross Sectional untuk metode kuantitatif dengan uji hipotesis dan metode kuantitaf untuk mengetahui peran manajemen dalam peningkatan mutu pelayanan kesehatan terhadap kepusasan pasien dan kepuasan pasien terhadap minat memanfaatkan kembali puskesmas. Hasil penelitian menunjukan terdapat hubungan yang signifikan mutu pelayanan kesehatan terhadap kepusasan pasien dan kepuasan pasien terhadap minat memanfaatkan kembali puskesmas di Kota Bengkulu (p=0,001). Hasil penelitian kualitatif menunjukan pelayanan yang diberikan sudah baik karena petugas puskesmas menjalankan upaya demensi kualitas pelayanan terutama dari segi dimensi empati dan bukti fisik. Meskipun demikian, sebaiknya pihak puskesmas harus terus melakukan pembenahan untuk meningkatkan kinerja pelayanan guna memenuhi keinginan dan kebutuhan pasien dengan upaya secara kontinyu dan terprogram.